PWE-041 Alteration in small bowel motility, gut peptides and patient's symptoms in active crohn's disease. (8th June 2018) - Moran, Gordon; Khalaf, Asseel; Hoad, Caroline; Menys, Alex; Radford, Shellie; Nowak, Adam; Paparo, Stephen; Lingaya, Melanie; Falcone, Yirga; Singh, Gulzar; Taylor, Stuart; Spiller, Robin; et al.
Abstract : Introduction: Intestinal inflammation in Crohn's disease (CD) is associated with an increase in Polypeptide YY (PYY), Glucagon-like peptide 1 (GLP-1) and cholecystokinin (CCK). CD patients experience postprandial fullness and nausea. These symptoms may be linked to the increase in plasma gut peptides levels and alterations in intestinal motility. Our aims are to quantify gut peptide, small bowel motility and patient symptom response to a standard test meal using Magnetic Resonance Imaging (MRI). Methods: Subjects underwent baseline and postprandial MRI scans, symptom questionnaires and blood sampling (GLP-1, PYY, CCK) at intervals for 270 min following a test meal: soup (400 g) (Heinz, Wigan, UK); (kcal) 51, protein 1.5 g, carbohydrate 4.7 g, fat 2.9 g per 100 g. MRI scans were performed using a 1.5T Philips Achieva MRI scanner. Gastric volume, small bowel water content (SBWC) and small bowel motility were assessed using MRI. Patients also underwent a standard contrast enhanced clinical MR enterography (MRE) and MaRIA score applied to quantify disease activity. All subjects gave informed written consent. Trial registration number: NCT03052465 . Data is presented as mean ±SEM. Results: CD patients showed a significantly (p≤0.05) slower fasting small bowel motility (50±6 a.u.) compared to HV (77±10 a.u.). Postprandial SBWC was significantly greater in CD than HV (measured as area under the curve CD: 18452, HV: 13760, p≤0.05). Fasting PYY (CD: 236±16 pg/mL, HV: 118±11 pg/mL, p≤0.0001) and GLP-1 (CD: 50±8 µg/mL HV: 13±3 µg/mL, p≤0.0001) were significantly higher in CD compared to HV with this difference persisting at each time point of the study (p≤0.0001). The meal induced a significant increase (p≤0.0001) in fullness, bloating and abdominal pain scores in patients (28±4 mm, 22±3 mm and 12±2 mm respectively) compared to HV (12±4 mm, 3±3 mm and 1±2 mm respectively). No differences were noted in gastric volumes, CCK concentration and postprandial motility. Conclusion: The decrease in fasting small bowel motility noted in CD may be ascribed to the increased fasting GI peptides. Understanding the physiological changes in disease groups will allow us to identify the key biomarkers for pharmacological modulation to improve patient symptoms.